Analisis Efektivitas dan Kontribusi Penerimaan Pajak Bumi dan Bangunan Dalam Meningkatkan Pendapatan Asli Daerah di Kota Medan Tahun 2016-2020 - Faizatun Nisa; Muhammad Arif (LPPM IAI Nasional Laa Roiba Bogor, 2022)
The purpose of this study was to see whether PBB revenue in Medan City within a period of five years (2016-2020) had effectively contributed well and could increase Regional Original Income. Moreover, to find out the obstacles faced by officers in the process of collecting taxes to taxpayers. This study uses a qualitative descriptive analysis method by collecting, compiling, processing, and analyzing numerical data in order to provide an overview of a certain situation so that conclusions can be drawn. The data collection method used is the documentation method which is carried out by taking documentation on the PBB target report obtained from the Medan City BPPRD office. The results of the study show that the realization of the Land and Building Tax within a period of five years, namely in 2016-2020 hasn’t reached the target. Based on the acquisition of secondary data, the average effectiveness calculation result from 2016-2020 is 88% entered in the criteria of Enough Effective. Based on the calculation of the effectiveness of the contribution, the average PBB result for 2016-2020 is 28.7% with the criteria being quite effective. Obstacles that arise in tax collection include the low level of public awareness of the usefulness of taxes so that they are still reluctant to register or pay their taxpayers, there is still a sense of openness from the public regarding their taxpayer data. Keywords: Poverty Tax; Effectiveness; Contribution; Local Native Income